2014
DOI: 10.1038/cgt.2014.56
|View full text |Cite
|
Sign up to set email alerts
|

Novel and enhanced anti-melanoma DNA vaccine targeting the tyrosinase protein inhibits myeloid-derived suppressor cells and tumor growth in a syngeneic prophylactic and therapeutic murine model

Abstract: Melanoma is the most deadly type of skin cancer, constituting annually ∼ 75% of all cutaneous cancer-related deaths due to metastatic spread. Currently, because of metastatic spread, there are no effective treatment options for late-stage metastatic melanoma patients. Studies over the past two decades have provided insight into several complex molecular mechanisms as to how these malignancies evade immunological control, indicating the importance of immune escape or suppression for tumor survival. Thus, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…The lag time of about one week compared to direct subunit protein vaccination may be due to the fact that DNA vaccine has to generate the protein first and the protein then will induce the antibody. Conventional intramuscular vaccination schedule with DNA vaccines for optimal CD8 + T cell activity is day 0, 14, 28 and harvesting the splenocytes at day 35 to 42 [47,50,51]. These studies did not report the kinetics of T cell generations with time.…”
Section: Kinetics Of Antigen Specific Cd8mentioning
confidence: 78%
“…The lag time of about one week compared to direct subunit protein vaccination may be due to the fact that DNA vaccine has to generate the protein first and the protein then will induce the antibody. Conventional intramuscular vaccination schedule with DNA vaccines for optimal CD8 + T cell activity is day 0, 14, 28 and harvesting the splenocytes at day 35 to 42 [47,50,51]. These studies did not report the kinetics of T cell generations with time.…”
Section: Kinetics Of Antigen Specific Cd8mentioning
confidence: 78%
“…A potential influence of suppressor cells on the effectiveness of immunization is particularly suspected in advanced ages, since it is generally accepted that both regulatory T cells and MDSC increase with aging 33, 34 . On the other hand, cancer immunization might also modulate the suppressor cells representation; in this context, it has been recently shown that an anti melanoma DNA vaccine induced a robust and broad immune response and inhibited MDSCs and tumour growth 35 . Interestingly, in our study, the inability of BI to modulate the number of either T reg cells or MDSCs, suggests that the beneficial effect of BI was not reduced by a potential BI-related induction of suppressor cells, and that the BI effectiveness was not related to a reduced representation of these two suppressor populations.…”
Section: Discussionmentioning
confidence: 99%
“…118,119 An enhanced human tyrosinase DNA antigen was designed using a codon-and RNA-optimized approach and it was found to reduce the frequencies of myeloidderived suppressor cells in a syngeneic prophylactic and therapeutic murine model, suggesting a potential strategy for preventing tumor progression and immune escape. 120 Despite the promising results obtained in animal models, it is not easy to evoke sufficient immune responses for significant clinical benefits. 121,122 Because checkpoint inhibitor immunotherapy has played an essential role in melanoma treatment, vaccination with DNA encoding melanoma-specific antigens is promising for adjuvant therapy in combination with CTLA-4 or PD1/PD-L1 blockade in late-stage diseases.…”
Section: Melanoma-specific Antigenmentioning
confidence: 99%